2010
DOI: 10.3899/jrheum.091236
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Rheumatoid Factor Isotypes and IgG Anti-Cyclic Citrullinated Peptide Antibodies

Abstract: Objective.To validate in a general patient population (GPP) the clinical value of measuring rheumatoid factor (RF) isotypes in relationship to IgG anti-cyclic citrullinated peptide (CCP) antibodies (CCP2 and CCP3).Methods.Serum samples were obtained as follows: 1021 GPP, for whom RF was ordered for diagnosis, 137 with rheumatoid arthritis (RA), 100 healthy blood donors (HBD), and 50 with systemic lupus erythematosus. Turbidimetry and ELISA were utilized for RF screening, and individual RF isotypes and IgG anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
(48 reference statements)
1
22
0
1
Order By: Relevance
“…We identified 797 articles, of which 17 met the inclusion criteria [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. There were 1952 RA patients selected from Europe, Americas and Asia in the remaining 17 articles that were eventually available for this meta-analysis (see Table 1).…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
“…We identified 797 articles, of which 17 met the inclusion criteria [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. There were 1952 RA patients selected from Europe, Americas and Asia in the remaining 17 articles that were eventually available for this meta-analysis (see Table 1).…”
Section: Search Results and Characteristics Of The Studiesmentioning
confidence: 99%
“…A study performed by Jaskowski et al [20] found no statistically significant difference in sensitivity and specificity between anti-CCP3 and anti-CCP2. Instead, they showed that anti-CCP3 antibodies were more prevalent than anti-CCP2 antibodies in RF-negative RA patients.…”
Section: Introduction/objectivesmentioning
confidence: 99%
“…Various serum biomarkers were studied with regard to diagnosing RA. Anti-CCP autoantibodies are currently considered to be the best biomarkers in the early diagnosis of RA [30][31][32][33]. Specifically, we demonstrated that the SERS-based immunosensor is more sensitive at detecting human anti-CCP than is the commercially available enzymelinked immunosorbent assays (ELISA).…”
Section: Introductionmentioning
confidence: 99%